Migracje z Ukrainy do Unii Europejskiej z perspektywy ryzyka (Politeja, 2016)
Ukrainian migration to the European Union from the risk perspectiveThe aim of this paper is to analyse, through the prism of risk theories, migration from Ukraine to the European Union in a multidimensional perspective. Risks taken by different actors associated with migration along this route have been considered. At the micro-level these are risks borne by Ukrainian migrants themselves. At the macro-level these are risks borne by both states of destination and origin. The concept of risk is the most suitable theoretical approach to be applied in the case of analyzing Eastern European migration. Migration to the fortress “Europe” creates many risks for the migrants and is treated as a challenge by the state actors. At the same time, it cannot be regard as a as a security threat. It is very modest both in the numbers and possible adverse consequences for all stakeholders involved. The article pays special attention to the issue of possible risks related to the eruption of armed conflict in Eastern Europe. It argues that those risks have grown but not significantly and the most affected actor is the Ukrainian state itself, who in a long-term perspective may experience dramatic demographic challenges. Both migrants as well the EU destination states may be at higher risk only in a case of serious destabilization at the whole Ukrainian territory.